2015
DOI: 10.3390/ijms161024600
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Omega-3 Fatty Acid Supplementation on Cognition and Mood in Individuals with Cognitive Impairment and Probable Alzheimer’s Disease: A Randomised Controlled Trial

Abstract: Findings from epidemiological and observational studies have indicated that diets high in omega-3 polyunsaturated fatty acids (PUFAs) such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) may reduce the risk of cognitive decline and Alzheimer’s disease (AD). To determine if increasing intake of DHA and EPA through supplementation is beneficial to cognition and mood in individuals with cognitive impairment no dementia (CIND) or Alzheimer’s disease (AD) a four month, randomised, double-blind, placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 46 publications
2
87
0
2
Order By: Relevance
“…Improved memory performance in subjects with mild Alzheimer's disease was reported with 1.5 g EPA+DHA/day for 6 months (251) . However, a number of other studies using various doses and ratios of EPA and DHA reported no effect on cognitive performance in people with Alzheimer's disease (252)(253)(254)(255)(256)(257) . Meta-analyses provide a mixed view of the findings for n-3 fatty acid treatment in the area of cognitive impairment, reflecting the mixed findings from individual trials.…”
Section: Neurocognitive Healthmentioning
confidence: 99%
“…Improved memory performance in subjects with mild Alzheimer's disease was reported with 1.5 g EPA+DHA/day for 6 months (251) . However, a number of other studies using various doses and ratios of EPA and DHA reported no effect on cognitive performance in people with Alzheimer's disease (252)(253)(254)(255)(256)(257) . Meta-analyses provide a mixed view of the findings for n-3 fatty acid treatment in the area of cognitive impairment, reflecting the mixed findings from individual trials.…”
Section: Neurocognitive Healthmentioning
confidence: 99%
“…The role of fatty acids such as DHA and EPA in AD pathogenesis is also clarified to a certain extent by the foregoing data. The association of composite indices comprising of various ratios of PlsEtn and PtdEtn species bearing polyunsaturated fatty acids at sn‐2 position (DHA, adrenic acid, and EPA) with cognitive scores and AD diagnosis appear to confirm early studies on the association of these fatty acids with AD and might explain why interventional studies using these fatty acid preparations (vs. phospholipids bearing these fatty acids) failed [66,67]. It seems more likely that rather than the specific fatty acid such as DHA or EPA, the specific molecular configuration of the phospholipids these fatty acids are associated with is more important than fatty acids itself.…”
Section: Discussionmentioning
confidence: 70%
“…EPA and DHA supplementation increases RBC n-3 PUFA content, working memory performance, and blood oxygen level-dependent signal in the posterior cingulate cortex during greater working memory load in older adults with subjective memory impairment [22]. However, another RCT confirmed an overall negligible benefit of n-3 PUFA supplementation for individuals with CIND or AD [23]. Eriksdotter et al demonstrated the dose-response relationships between plasma levels of n-3 PUFA and preservation of cognition [24].…”
Section: The Intervention Studies Which Investigated the Association mentioning
confidence: 99%